PENGARUH PEMANFAATAN MEDIA GAMBAR GUNA MEMAHAMKAN KONSEP BERHITUNG DI SEKOLAH DASAR - Prihastari, Ema Butsi (Widya Wacana: Jurnal Ilmiah, 2016)
One of professional skills required to be developed is an approriate and effective learningmethod. Learning activities in the classroom will be effective when the teacher uses instructionalmedia to invest the concept, so it can delete verbalitic concept, in particular in counting learning.This experiment research aims to know the influence of visual media on the counting concept ofthe first grade student of elementary school at Surakarta city. The data analysis acquired thitung1,88 is greater than ttabel 1,68. Therefore, there is an influence of visual media toward countingconcept of the first grade student of elementary school.Keyword : influece, drawing, count